2019
DOI: 10.1016/j.eist.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

System dynamics modelling and simulation for sociotechnical transitions research

Abstract: Sociotechnical transitions is an emerging research area that uses several methods, amongst which case study and simulation models are often applied. This paper focuses on system dynamics modelling and simulation research and its potential contribution to transition research. Current system dynamics work comes from a wide range of disciplines and spans across the micro, meso, and macro levels which transitions are predominantly analysed along. This overlap carries considerable potential as a conceptual and theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 164 publications
(221 reference statements)
0
42
0
1
Order By: Relevance
“…The CE actions of managers need to be guided by systems-thinking-based tools that are able to show the implications of one system level on another system level (Papachristos, 2019). For example, the resource efficiency of a product is not just determined by the product's characteristics over its lifecycle.…”
Section: Research Motivationmentioning
confidence: 99%
“…The CE actions of managers need to be guided by systems-thinking-based tools that are able to show the implications of one system level on another system level (Papachristos, 2019). For example, the resource efficiency of a product is not just determined by the product's characteristics over its lifecycle.…”
Section: Research Motivationmentioning
confidence: 99%
“…Consequently, important elements such as the systems' internal feedback, nonlinear relationships, and inability to process new information or decisions within the time available are not considered. These omissions create temporal delays between the actions taken in the systems and the verification of the results and/or consequences (Papachristos, 2019). In other words, the causes and their effects are separated in time, which, when added to the multiple relationships among the variables involved, undermines the understanding needed to determine exactly what events triggered the systems' behavior (Sterman, 2002;Papachristos, 2019).…”
Section: System Dynamicsmentioning
confidence: 99%
“…The SD approach facilitates the identification of structural elements and policies that lead to decisions, successfully overcoming nonlinear relationships' "noisy" environment generated partly by decision makers' perceptual and cognitive limitations (Papachristos, 2019). This approach seeks to split the decision-support system into smaller fragments, examining each element as a way to analyze change impacts and results in terms of the remaining elements under study (Sederati et al, 2019).…”
Section: System Dynamicsmentioning
confidence: 99%
“…To evaluate sustainability transition pathways, it is argued that no single perspective or discipline will be adequate due to the multi-dimensional nature of sustainability transitions that requires integration of multiple theories and approaches to generate useful knowledge [13][14][15][16][17]. To gain a broader perspective of sustainability transitions, integrated approaches and linkages between individual forms of analysis have been proposed [16][17][18]. There are a number of integrated approaches that look at HEI sustainability transitions [14,[19][20][21], but these studies assess individual campus sustainability only, and a literature search found no relevant studies in relation to the HEI sector.…”
Section: Integrated Approaches Surrounding Sustainability Transitionsmentioning
confidence: 99%